IMS-Dengue Survey (Integrated management strategy for dengue) as a Diagnosis of Village Readiness in Realizing Integrated Dengue Prevention and Control - Siyam, Nur; Cahyati, Widya Hary; Rosha, Putri Tiara; Hanan, Latifa; Nurrochmah, Siwi Amru; Sholehawati, Ardhita; Aviana, Rhanindra; Mariezko, Arnayla Nezza; Lestari, Niken (Jurnal Kesehatan Masyarakat, 2024)
In 2022, Semarang City experienced a 4-fold increase in dengue cases with IR: 51.7/100,000 residents, CFR: 3.8%. The purpose of the study was to determine the readiness of village-based dengue control based on IMS-dengue criteria in realizing integrated dengue prevention and control. The study was conducted in Bandarharjo Village, a high-risk community on the outskirts of Semarang City, consisting of 30 cadres and 83 people who had stayed for at least 6 months. Samples were taken using a purposive sampling technique. Analytical survey research, data collection with questionnaires, and observation checklists. The results of an integrated dengue control survey in households show that the use of mosquito repellent is still high (94.0%) and the use of larvicide to prevent mosquitoes in water reservoirs that are difficult to clean is preferred. Good practices in the use of mosquito nets during early morning sleep 42.2%, rearing larval predatory fish 61.4%, and the use of mosquito repellent plants (39.8%) are still quite minimal. Factors related to dengue control practices are perceptions of the seriousness of dengue disease in the community.